DESIGN OF A MOBILE AND WEB-BASED ACADEMIC INFORMATION SYSTEM (Case Study: SD Negeri 02 Pegiringan) - Ahsin Apri Aenul Yaqin; Irma Handayani (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2023)
SD Negeri 02 Pegiringan is one of the elementary schools in Pemalang. Currently, SD Negeri 02 Pegiringan is still using the 2013 elementary school curriculum, and has earned an A accreditation rating in 2022, the problem faced by SD Negeri 02 Pegiringan at this time is that parents cannot always monitor their children's grades, so they are less aware of their development. In addition, the report card data processing process still relies on the use of Excel manually. Based on these problems, this research builds a mobile web-based academic information system application. With this academic information system, it can simplify the process of checking, recording, and reporting student grade data in a computerized manner. The system design in the application utilizes the UML (Unified Modeling Language) methodology, and will be implemented with PHP (Pear Hypertext Preprocessor) as a programming language for web and Dart for Android, MySQL as a database server, with the data processed is student data, teacher data, grade data, class data, grade data, and subject data.